2020
DOI: 10.3758/s13414-020-02070-7
|View full text |Cite
|
Sign up to set email alerts
|

Creating a network of importance: The particular effects of self-relevance on stimulus processing

Abstract: Several factors guide our attention and the way we process our surroundings. In that regard, there is an ongoing debate about the way we are influenced by stimuli that have a particular self-relevance for us. Recent findings suggest that self-relevance does not always capture our attention automatically. Instead, an interpretation of the literature might be that self-relevance serves as an associative advantage facilitating the integration of relevant stimuli into the self-concept. We compared the effect of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 75 publications
1
29
0
1
Order By: Relevance
“…Across a diverse range of experimental tasks, it has been demonstrated that processing stimuli associated with the self can modulate attention (Sui et al, 2009), perception (Golubickis et al, 2017;Sui et al, 2012), memory (Rogers et al, 1977;Turk et al, 2008), and decision-making (Liu et al, 2016). Studies using a perceptual-matching task to examine the Self-Prioritization Effect (SPE; Sui et al, 2012) have demonstrated that effects of self-relevance can be dissociated (at least in part) from those of other response-facilitating factors, such as stimulus familiarity (Sui et al, 2012;Woźniak & Knoblich, 2019), stimulus reward value (e.g., Qian et al, 2019;Yankouskaya et al, 2017), emotional valence (Schäfer et al, 2020;Stolte et al, 2015), and semantic elaboration . Distinct neural circuitry has also been demonstrated to underpin the self-advantage in the matching task Yankouskaya et al, 2017).…”
mentioning
confidence: 99%
“…Across a diverse range of experimental tasks, it has been demonstrated that processing stimuli associated with the self can modulate attention (Sui et al, 2009), perception (Golubickis et al, 2017;Sui et al, 2012), memory (Rogers et al, 1977;Turk et al, 2008), and decision-making (Liu et al, 2016). Studies using a perceptual-matching task to examine the Self-Prioritization Effect (SPE; Sui et al, 2012) have demonstrated that effects of self-relevance can be dissociated (at least in part) from those of other response-facilitating factors, such as stimulus familiarity (Sui et al, 2012;Woźniak & Knoblich, 2019), stimulus reward value (e.g., Qian et al, 2019;Yankouskaya et al, 2017), emotional valence (Schäfer et al, 2020;Stolte et al, 2015), and semantic elaboration . Distinct neural circuitry has also been demonstrated to underpin the self-advantage in the matching task Yankouskaya et al, 2017).…”
mentioning
confidence: 99%
“…However, consistent with the present findings, previous studies have found that geometric shapes could be expanded to the self by tagging a neutral shape with a self-relevant label and could obtain behavioral self-bias (Sui et al, 2012 , 2013 ). More importantly, the effect has meanwhile been replicated by other laboratories (Stein et al, 2016 ; Wozniak et al, 2018 ; Schäfer et al, 2020 ), in which the effects have been reasonably interpreted by using the BRAC framework (Schäfer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 73%
“…Recently, BRAC has been applied to interpret the effects on self-relevance. In research examining the effects of self-reference on stimulus processing, Schäfer et al ( 2020 ) have argued that once stimuli are perceived as being relevant for our self, self-relevance serves to create a network of those contents and elements by binding them together, and the self would be represented by bindings of particular features. In the present study, it is a sentence “Mike uses blue AGSs and Joe uses red AGSs” that binds the features, such as the color and shapes of AGSs to the self or another person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study has suggested that the SPE is located at a later, post‐perceptual stage of information processing (Janczyk, Humphreys, & Sui, 2019). Other studies have, though, challenged the perceptual account in favour of a memory advantage (Reuther & Chakravarthi, 2017) or else a learning (Fuentes, Sui, Estévez, & Humphreys, 2016) or association advantage (Schäfer, Wentura, & Frings, 2020; Sui & Humphreys, 2015) due to the self‐relevance of the stimuli instead.…”
Section: Introductionmentioning
confidence: 99%